Comparison of the physical stabilities and oxidation of lipids and proteins in natural and polyphenol-modified soybean protein isolate-stabilized emulsions. (December 2022) - Yan, Shizhang; Yao, Yuxue; Xie, Xuan; Zhang, Shuang; Huang, Yuyang; Zhu, Huaping; Li, Yang; Qi, Baokun
Graphical abstract: Highlights: The protein–phenolic compound conjugates are prepared by three methods. The structures and antioxidant properties of these conjugates were investigated. The physical stabilities and oxidation properties of their emulsions were examined. The conjugates prepared via one of the methods slowed lipid and protein oxidation. The conjugates prepared via the other two methods promoted protein oxidation. Abstract: Oil-in-water emulsions are widely used in the food industry; however, lipids are often easily oxidized, which may adversely affect food quality. Herein, we investigated the effects of alkali treatment, free radical induction, and carbodiimide hydrochloride (EDC)/ N -hydroxysuccinimide (NHS)-mediated synthetic methods on the structures and antioxidant properties of soy protein isolate (SPI)–gallic acid (GA) conjugates and the physical stabilities and protein–lipid co-oxidation properties of the resulting emulsions. These three methods are well established; however, their effects on the same protein–phenolic compound system have not been directly compared. Additionally, the co-oxidation of proteins and oils in emulsions remains unexplored. Alkali treatment yielded superior antioxidant properties compared to those obtained using free radicals or EDC/NHS, as this method was more likely to yield CS bonds and resulted in an increased quantity of grafted GA. Spectroscopic analysis showed that alkali treatment promoted GA oxidation and thereby increased GA-protein interactions and the quenching of tryptophan fluorescence. Correspondingly, EDC/NHS-mediated conjugation retained the activity of the hydroxyl groups of GA to the largest extent. Moreover, the grafting of GA improved the physical and oxidative stabilities of the emulsions. In particular, EDC/NHS-mediated conjugation produced an emulsion with optimal oxidative stability owing to its effective inhibition of lipid and protein oxidation. Conversely, the conjugates synthesized via alkali treatment and free radical induction displayed less inhibition of lipid oxidation and promoted protein oxidation. In conclusion, optimized protein–phenolic compound conjugates for use in developing nutritional fortification products with longer shelf lives can be obtained by using appropriate synthetic methods.